Silver absorption and toxicity evaluation of silver wound dressings in 40 patients with chronic wounds. (1st June 2018) - Brouillard, C.; Bursztejn, A.‐C.; Latarche, C.; Cuny, J.‐F.; Truchetet, F.; Goullé, J.‐P.; Schmutz, J.‐L.
Abstract: Background: Silver‐containing dressings are considered to be safe even though there have been some reports of complications, including argyria and various organ system dysfunctions. Despite the widespread use of silver dressings, little research has been done regarding the absorption and toxicity of silver. Objective: We aimed to study the systemic absorption of silver in patients with chronic inflammatory wounds and to determine associated factors of systemic silver absorption and evaluated its association with silver toxicity. Patients and method: Prospective, longitudinal, observational, multicentre, open‐label pilot study. Patients from the Dermatology Departments of Lorraine (France) with the following inclusion criteria: (i) a chronic wound of more than 6 weeks and (ii) an ulcer needing silver‐containing dressing were included. Before and after 28 days of treatment, clinical characteristics of the wound were recorded; hemogram, hepatic and renal functions, albumin sera and serum silver level were measured. Results: Half of the cases displayed raised levels of silver after 1 month of treatment. Predictive factors for systemic silver absorption were wound area, anaemia and malnutrition with anaemia and malnutrition confirmed on multivariate analysis. Wound vascularization may also play a role, as a higher absorption was observed in cases of wound granulation without arterial components. No toxicity was detected. This work has also emphasized the slow elimination of silver from the body. Conclusion: Both long‐term application and iterative treatments with silver dressings should be discouraged, especially in the elderly, who often suffer from malnutrition and anaemia to avoid potential cumulative toxicity.